The effect of physical fitness, economic status and learning motivation on learning outcomes (PJOK) at Smp El-Ma'arif Boarding School West Pasaman Regency - Andika, Yudhia; Firdaus, Kamal; Irawan, Roma; Pranoto, Nuridin Widya; Zarya, Fiky (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to determine the influence between physical fitness, economic status, and motivation on PJOK learning outcomes at SMP El-Ma'arif Boarding School West Pasaman Regency. This research method is a quantitative method using a Path Analysis approach. The population in this study was all students at SMP El-Ma'arif Boarding School West Pasaman Regency which amounted to 46 students. The sampling technique was carried out by means of total sampling, with a total sample of 46 people. Data was collected using questionnaires to measure self-confidence and learning motivation, TKPN tests to obtain physical fitness data of students and primary data were used to see learning outcomes obtained by students in the even semester of the 2023/2024 school year. The results of research and data analysis show that: (1) Physical fitness has a direct effect on learning outcomes because the sig value = 0.026 is smaller than the probability value of 0.05, affecting 9.80%. (2) Economic status directly affects learning outcomes obtained GIS value = 0.015 smaller than the significant value of 0.05, influential by 12.30%. (3) Learning motivation has a direct effect on learning outcomes because the value of sig = 0.007 is smaller than the probability value of 0.05, affecting 16.73%. This study concluded that physical fitness, economic status, and learning motivation directly have a significant effect on PJOK learning outcomes at SMP El-Ma'arif Boarding School West Pasaman Regency.